A tendon-simulating hierarchical spiral luminescent suture with photodynamic antibacterial and fluorescent tracing functions and a preparation method and application thereof
Patent Information
- Application Number
- CN202611053369.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]针对现有缝合线无法同时实现非抗生素依赖的光动力抗菌、皮下荧光示踪动态监测以及高张力组织适配性缝合的技术问题
本发明提供的聚集诱导发光光敏剂,创新性地采用了给体-π-受体(D-π-A)构型。该特定的扭曲骨架结构不仅彻底克服了传统荧光染料的聚集猝灭(ACQ)效应,实现了在固态或聚集态下的显著荧光增强(即AIE特性);更关键的是,其D-π-A结构有效促进了分子内电荷转移(ICT)并显著提升了系间窜越(ISC)效率,从而极大提高了活性氧(ROS)的量子产率。这使得该光敏剂在缝合线的固态基质中,既能稳定发射高对比度的明亮荧光,又具备极高的光激发产生活性氧的能力,从底层分子设计上为缝合线同时实现皮下示踪与高效光动力抗菌提供了核心功能材料基础。
Smart Images

Figure CN122978110A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a tendon-like layered spiral luminescent suture with photodynamic antibacterial and fluorescent tracing functions, its preparation method, and its application. Background Technology
[0002] Postoperative wound management relies heavily on surgical sutures, one of the most widely used medical devices, playing a crucial role in tissue occlusion, hemostasis, and wound healing in almost all surgical procedures. Traditional sutures, whether non-absorbable (e.g., nylon, polypropylene) or absorbable (e.g., polylactic acid), offer limited antibacterial protection and provide no visual feedback once embedded in the tissue. While attempts have been made to reduce infection risk by coating the sutures with antibiotics or metal-based formulations, these methods suffer from uncontrollable drug release, potential drug resistance, and biosafety concerns. Similarly, postoperative assessment of suture condition relies on less sensitive indirect clinical signs or imaging examinations, often leading to delayed detection of suture breakage or wound dehiscence. Existing antibacterial sutures often employ surface coatings (antibiotics, silver ions, etc.), which present problems such as uncontrollable release, easy development of drug resistance, and potential biotoxicity. Therefore, developing a multifunctional intelligent suture capable of both active antibacterial action and dynamic subcutaneous tracking is of great significance.
[0003] Despite decades of material innovation, from natural fibers (silk, catgut) to synthetic polymers (nylon, polylactic acid, poly(glycolic acid)), two persistent challenges continue to limit clinical efficacy: surgical site infection caused by bacterial adhesion and colonization, and the inability to non-invasively monitor the integrity of subcutaneous sutures during healing, particularly the risk of secondary wound dehiscence due to degradation or mechanical failure. Sutures, especially multi-stranded sutures, provide a favorable surface for bacterial adhesion and biofilm formation, leading to persistent bacterial colonization and resistance to host defense mechanisms and systemic antibiotics. Pathogens such as Staphylococcus aureus (including MRSA) and Escherichia coli can proliferate along suture pathways, causing severe inflammation, delaying wound healing, and in severe cases, leading to suture failure and wound dehiscence. Although methods for coating suture surfaces with antibiotics or silver nanoparticles have been explored, these methods suffer from limited duration of activity, potential promotion of antimicrobial resistance, and potential local toxicity. Furthermore, a frequently overlooked challenge is the inability to non-invasively monitor the integrity and degradation status of sutures after subcutaneous implantation. Once buried deep within the tissue, traditional sutures become invisible, preventing clinicians from directly assessing their continuity, breakage, or degradation kinetics. This "blind period" poses significant risks: undetected suture breakage or premature loss of mechanical integrity can lead to secondary wound dehiscence, bleeding, or delayed reoperation—complications particularly challenging in deep or minimally invasive surgeries. Current imaging techniques (such as ultrasound and CT) lack sufficient contrast to reliably visualize fine suture fibers, and there is currently no real-time, patient-friendly method to track postoperative suture status. Therefore, a suture that can both prevent postoperative infections (SSIs) and enable dynamic subcutaneous tracking would mark a major advancement in postoperative wound management.
[0004] Furthermore, many existing collagen-based bio-sutures use molecularly dissolved collagen or gelatin as a matrix. Because this disrupts the mesoscale assembly structure of natural collagen, they suffer from extremely low mechanical strength and rapid degradation, failing to meet the suturing requirements of high-tension tissues. Recent research has found that collagen aggregates (CAs) that retain the mesoscale fibrous assembly structure of natural collagen can serve as building blocks. Through wet spinning, collagen fibers with excellent mechanical properties can be prepared, exhibiting significantly superior breaking strength and toughness compared to traditional dissolved collagen spun fibers (“Robust collagen filaments with aligned mesoscale aggregates as building blocks for surgical sutures”, Journal of Colloid and Interface Science, Jiaqi Li et al. 10.1016 / j.jcis.2025.139751). This discovery provides a new approach for the development of high-performance collagen-based sutures.
[0005] In summary, existing technologies (such as surface-coated sutures and traditional collagen-based sutures) mainly face three major technical problems that urgently need to be addressed: First, traditional antibacterial methods rely heavily on the release of antibiotics or metal ions, which is uncontrollable and easily induces bacterial resistance and local tissue toxicity. Second, once the suture is implanted deep under the skin, it enters a "visual blind spot," making it impossible to monitor the degradation kinetics and mechanical integrity of the suture in real time during the healing process using non-invasive methods, resulting in a very high risk of hidden wound dehiscence. Third, existing collagen-based materials often destroy the mesoscale assembly structure of natural collagen fibers during the preparation process, leading to extremely low mechanical strength and rapid degradation, which cannot meet the suturing and load-bearing requirements of high-tension tissues.
[0006] Therefore, it is of great significance to develop a new type of intelligent suture that combines antibacterial treatment, tissue repair promotion, and subcutaneous visualization monitoring functions. Summary of the Invention
[0007] To address the technical challenges of existing sutures in simultaneously achieving non-antibiotic-dependent photodynamic antibacterial activity, subcutaneous fluorescence tracking and dynamic monitoring, and high-tension tissue-adaptive suturing, this invention aims to provide a tendon-inspired layered spiral luminescent suture with photodynamic antibacterial and fluorescence tracking functions, along with its preparation method and applications. This invention integrates photodynamic non-antibiotic targeted antibacterial activity, subcutaneous in-situ fluorescence tracking, and high-strength, biomimetic mechanics. It achieves non-invasive monitoring and photodynamic sterilization by introducing a photosensitizer with aggregation-induced emission (AIE) properties. Simultaneously, it employs a layered spiral twisting process to reshape the biomimetic structure using collagen aggregates (CAs) that retain their natural mesoscopic scale, overcoming the technical bottlenecks of traditional smart sutures' single function and weak mechanical properties.
[0008] To achieve the above objectives, the present invention employs the following technical solution: In a first aspect, the present invention provides an aggregation-induced emission (AIE) photosensitizer having the following structural formula: .
[0009] The photosensitizer is a compound with a donor-π-acceptor structure. This structural design promotes intramolecular charge transfer effects, improves intersystem crossing efficiency, and thus enhances the quantum yield of reactive oxygen species. Simultaneously, the distorted conformation of the D-π-A backbone effectively suppresses concentration quenching, allowing the photosensitizer to maintain high fluorescence quantum yield and reactive oxygen species generation capacity even in a solid-state aggregated state, ensuring stable and reliable photodynamic performance of the suture in the complex in vivo environment.
[0010] Secondly, the present invention provides a tendon-like layered spiral luminescent suture, wherein the material of the suture comprises the aggregation-induced emission (AIE) photosensitizer described above.
[0011] The suture is composed of multiple nascent fibers twisted into a helical fiber bundle structure. The nascent fibers also include collagen aggregates and polyvinyl alcohol. The collagen aggregates retain the mesoscale fiber assembly structure of natural tendons. By using collagen aggregates that retain the natural mesoscale structure instead of molecular collagen, the poor mechanical properties of traditional dissolved collagen are solved. The helical bundle structure formed by twisting multiple nascent fibers simulates the hierarchical configuration of natural tendons, significantly enhancing interfiber bonding and load transfer efficiency. This gives the suture both high strength and good flexibility, meeting the suturing requirements of high-tension tissues.
[0012] The volume ratio of polyvinyl alcohol to collagen aggregates in the nascent fibers is 1~2:1; the number of twisted nascent fibers in the helical fiber bundle structure is 20-40.
[0013] Preferably, the volume ratio of polyvinyl alcohol to collagen aggregates in the nascent fibers is 2:1, and the number of twisted nascent fibers in the helical fiber bundle structure is 30. After twisting 30 fibers, the tensile strength reaches 5.45 times that of a single fiber, which ensures the mechanical reliability of the suture and controls the wire diameter to suit clinical suturing operations.
[0014] Thirdly, the present invention provides a method for preparing a tendon-like layered spiral luminescent suture, comprising the following steps: Step S1: Degrease and cut the animal tendon, treat it with acid, and then homogenize it to obtain a collagen aggregate dispersion; Step S2: Mix the polyvinyl alcohol solution with the collagen aggregate dispersion, add the aggregation-induced emission photosensitizer according to claim 1 or 2, stir evenly and then degas to obtain the spinning solution; Step S3: The spinning solution is extruded into a coagulation bath for phase separation and solidification, and then drawn, washed and dried to obtain nascent fibers; Step S4: Twist and twist the nascent fibers to form a helical fiber bundle structure, thus obtaining the suture.
[0015] In step S2, the volume ratio of the polyvinyl alcohol solution to the collagen aggregate dispersion is 1~2:1, and the concentration of the aggregation-induced emission photosensitizer in the spinning solution is 2 mM.
[0016] In step S3, the coagulation bath is a saturated sodium sulfate solution at 60~90℃.
[0017] Preferably, the coagulation bath is a saturated sodium sulfate solution at 70°C.
[0018] In step S4, the number of twisted strands is 20 to 40, and the twisting speed is 20 to 30 rpm.
[0019] Preferably, the number of twisted strands is 30, and the twisting speed is 25 rpm. Fourthly, the present invention provides the application of the aggregation-induced emission photosensitizer or the tendon-like layered spiral luminescent suture in the preparation of surgical suture materials.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The aggregation-induced emission photosensitizer provided by this invention innovatively adopts a donor-π-acceptor (D-π-A) configuration. This specific twisted backbone structure not only completely overcomes the aggregation quenching (ACQ) effect of traditional fluorescent dyes, achieving significant fluorescence enhancement (i.e., AIE characteristics) in the solid or aggregated state; more importantly, its D-π-A structure effectively promotes intramolecular charge transfer (ICT) and significantly improves intersystem crossing (ISC) efficiency, thereby greatly increasing the quantum yield of reactive oxygen species (ROS). This allows the photosensitizer to stably emit high-contrast bright fluorescence in the solid matrix of sutures, while also possessing extremely high photoexcitation capabilities to generate reactive oxygen species. From a fundamental molecular design perspective, this provides a core functional material basis for sutures to simultaneously achieve subcutaneous tracking and highly efficient photodynamic antibacterial activity.
[0021] The tendon-inspired spiral luminescent suture provided by this invention introduces an AIE photosensitizer into the suture material system, enabling the suture to inherit the fluorescence properties and photodynamic activity of the photosensitizer while achieving an organic integration of antibacterial and tracking functions. It can generate active oxygen to kill bacteria under light without antibiotics, avoiding the problem of drug resistance. At the same time, it endows the suture with subcutaneous visual tracking ability, breaking through the limitation of the single function of traditional sutures.
[0022] This invention provides a method for preparing a tendon-inspired layered helical luminescent suture. Through a four-step process—collagen aggregate extraction, spinning solution preparation, wet spinning, and twisting assembly—it achieves a perfect fusion of a macromolecular matrix and a small-molecule photosensitizer. The wet spinning process not only precisely preserves the integrity of the natural mesoscopic structure of the collagen aggregates but also effectively ensures the uniform doping and stable encapsulation of the AIE photosensitizer in the nascent fiber matrix. This induces solid-state aggregation to activate a strong AIE luminescence effect while preventing sudden release and leakage of the photosensitizer into the body fluid environment. The subsequent twisting assembly step deeply simulates the helical layered configuration of natural tendons, tightly aggregating dozens of nascent fibers. This significantly improves the load transfer efficiency between fibers, resulting in a significant increase in tensile strength (e.g., the tensile strength of 30 twisted fibers can reach over 211 MPa). This gives the final suture both biomimetic structural characteristics and excellent mechanical properties.
[0023] The application of aggregation-induced emission photosensitizers or tendon-inspired layered helical luminescent sutures provided by this invention in the preparation of clinical surgical suture materials has successfully constructed a refined wound management system integrating "high load-bearing capacity, active antibacterial activity, and intelligent tracking." The non-antibiotic-dependent photodynamic antibacterial and non-invasive transdermal fluorescence tracking capabilities provided by the AIE photosensitizer, combined with the excellent tensile strength brought by the biomimetic helical structure of collagen aggregates (CAs) and PVA, enable this suture to not only perfectly handle the suturing of high-tension tissues, but its controllable degradation period of approximately 30-35 days is also highly compatible with the natural healing process of human skin wounds. The deep synergy of these three components makes it particularly suitable for complex surgical scenarios with a high risk of infection by drug-resistant bacteria such as MRSA and a high likelihood of occult wound dehiscence. It provides clinicians with an intelligent medical device solution that can assess the healing status of deep wounds in real time and in situ, helping to detect the risk of wound dehiscence early. Attached Figure Description
[0024] Figure 1 This is the synthetic route for the AIE photosensitizer of the present invention.
[0025] Figure 2 The resonance hydrogen spectrum of the AIE photosensitizer of this invention ( 1 Characterization diagram (H NMR).
[0026] Figure 3 The fluorescence spectrum and AIE property characterization diagram of the AIE photosensitizer of the present invention in DMSO solutions with different water contents are shown.
[0027] Figure 4 This is a fluorescence spectrum of the AIE photosensitizer of the present invention, showing its ability to generate reactive oxygen species under white light irradiation.
[0028] Figure 5 The image shows the scanning electron microscope morphology of the luminescent suture of the present invention, where (i) is the surface morphology of a single nascent fiber and (ii) is the helical fiber bundle structure formed by twisting multiple fibers.
[0029] Figure 6 The figure shows the mechanical property test results of the luminescent suture of the present invention.
[0030] Figure 7 This is a diagram showing the in vitro antibacterial activity test results of the luminescent suture of the present invention.
[0031] Figure 8 This is a diagram showing the cell compatibility evaluation results of the luminescent suture of the present invention (L929 cell CCK-8 assay).
[0032] Figure 9 This is a graph showing the in vitro degradation performance of the luminescent suture of the present invention.
[0033] Figure 10This image shows the effect of the luminescent suture of the present invention on promoting healing in a full-thickness skin incision model of MRSA-infected rats.
[0034] Figure 11 This is a dynamic fluorescence tracking and degradation monitoring image of the luminescent suture of the present invention under the skin of mice. The top row is a photo taken under natural light, and the bottom row is a fluorescence photo taken under 365 nm ultraviolet light.
[0035] Figure 12 This is a HE-stained pathological section of subcutaneous wound tissue from the luminescent suture of the present invention. Detailed Implementation
[0036] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0037] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by those skilled in the art. For clarity, some terms used in this invention are defined as follows: Collagen aggregates (CAs) are collagen fiber fragments extracted from animal tendons using mild physical and chemical processing methods, retaining the mesoscopic (micrometer-level) assembly structure of natural collagen fibers. Unlike molecularly dissolved collagen or gelatin prepared by conventional methods, collagen aggregates exhibit a fibrous morphology with characteristic D-periodic striations under a microscope, typically 50-500 μm in length and approximately 1-10 μm in diameter. This structure endows collagen aggregates with superior mechanical properties and biological activity.
[0038] Aggregation-induced emission (AIE) refers to the photophysical phenomenon where fluorescent molecules emit little or no light in dilute solutions, but exhibit significantly enhanced fluorescence in aggregated states (such as solids, nanoparticles, or high-concentration solutions). Unlike the fluorescence quenching (ACQ) caused by aggregation of traditional fluorescent molecules, AIE molecules exhibit enhanced fluorescence emission in the aggregated state due to restricted intramolecular motion (RIM).
[0039] Photodynamic antimicrobial therapy utilizes photosensitizers excited by light of a specific wavelength. This excitation transfers energy to surrounding oxygen molecules, generating reactive oxygen species (ROS) such as singlet oxygen and superoxide anions. These ROS then oxidize and destroy bacterial cell membranes, proteins, and nucleic acids, leading to bacterial death. This method does not rely on antibiotics and is less likely to induce drug resistance.
[0040] Tendon-mimetic Hierarchical Helical Structure: This refers to the multi-level helical arrangement of collagen fiber bundles in natural tendons, ranging from micrometers to millimeters, achieved by twisting and bundling multiple nascent fibers. This structure comprises three levels: the first level consists of protofibrils composed of collagen aggregates; the second level consists of nascent fibers composed of protofibrils; and the third level consists of helical fiber bundles formed by twisting multiple nascent fibers, similar to the "protofibril-fiber-fiber bundle" hierarchical configuration of natural tendons.
[0041] Wet spinning refers to a fiber-forming method in which a polymer solution or sol (spinning solution) is extruded through a spinneret into a coagulation bath, where the exchange of solvent and non-solvent causes phase separation and solidification of the spinning solution. This method is suitable for temperature-sensitive biomolecular materials and can produce continuous fibers under mild conditions.
[0042] Unless otherwise stated, all reagents, materials and instruments used in the specific embodiments of the present invention are commercially available.
[0043] All reagents used in the embodiments of this invention were commercially available analytical grade reagents without further processing; the animal tendons used were fresh bovine tendons; the polyvinyl alcohol used was type 1788 (degree of hydrolysis 87-89%, molecular weight approximately 75,000), purchased from Shandong Keyuan Biochemical Co., Ltd.; the saturated sodium sulfate solution used was prepared from anhydrous sodium sulfate (analytical grade, Sinopharm Group) and deionized water. Staphylococcus aureus, MRSA, and Escherichia coli used in the embodiments of this invention were purchased from Shanghai Luwei Technology Co., Ltd. All experimental data are expressed as mean ± standard deviation, and each group had at least three replicates. Statistical analysis was performed using GraphPad Prism 8.0 software. Intergroup comparisons were performed using t-tests or one-way ANOVA, with P < 0.05 considered statistically significant.
[0044] Example 1: Synthesis of AIE photosensitizer This embodiment provides an aggregation-induced emission photosensitizer with a donor-π-acceptor structure, the structural formula of which is as follows: .
[0045] The preparation method of the fluorescent probe compound, such as Figure 1 As shown, the specific steps are as follows: 2-(4-(pyridin-4-ethynyl)phenyl)acetonitrile (200 mg, 0.92 mmol), 5-(4-(diphenylamino)phenyl)thiophene-2-carboxaldehyde (390 mg, 0.28 mmol), and NaOEt (19 mg, 0.28 mmol) were dissolved in ethanol (5 mL). The reaction mixture was refluxed in an oil bath at 80 °C for 12 h. The reaction was monitored by thin-layer chromatography (TLC, with hexane:ethyl acetate as the developing solvent, 1:1.5) until the spots of the two starting materials disappeared. After the reaction was completed, the reaction solution was cooled to room temperature, and the crude product precipitated. The crude product was purified by recrystallization from ethanol to obtain 40 mg of a pale yellow powder, with a yield of approximately 60%.
[0046] The prepared pale yellow powder product was characterized by NMR, and the results are as follows: Figure 2 As shown: the proton NMR spectrum data are: 1 ¹H NMR (600 MHz, Chloroform-d) δ 8.63–8.61 (m, 2H), 7.69–7.63 (m, 3H), 7.63–7.57 (m, 2H), 7.55–7.49 (m, 2H), 7.41–7.38 (m, 2H), 7.32–7.27 (m, 4H), 7.19–7.12 (m, 3H), 7.11–7.02 (m, 6H), 7.01–6.95 (m, 1H). Mass spectrometry data: ESI-MS: Calcd m / z: 56.18 [M+H] + . Example 2: AIE properties and reactive oxygen species generation capacity test of AIE photosensitizers This embodiment, based on Example 1, tests the relevant properties of the AIE photosensitizer prepared in Example 1. The specific tests are as follows: (1) AIE property test The AIE photosensitizer prepared in Example 1 was dissolved in dimethyl sulfoxide (DMSO) to prepare a 2 mM stock solution. Equal volumes of the stock solution were added to DMSO / water mixed solvents with different volume ratios to achieve a final photosensitizer concentration of 20 μM, with water volume fractions of 0%, 10%, 30%, 50%, 70%, 90%, and 99%, respectively. The fluorescence emission spectra (500-800 nm) of each solution were recorded using a fluorescence spectrophotometer (λex = 450 nm). Figure 3As shown, with the increase of the volume fraction of the undesirable solvent (water), the photosensitizer molecules gradually aggregate, and the fluorescence intensity at 592 nm gradually increases. When the water volume fraction reaches 99%, the fluorescence intensity is about 45 times stronger than that of the pure DMSO solution, indicating that the photosensitizer has typical aggregation-induced emission characteristics.
[0047] (2) Test of reactive oxygen species generation capacity 2,7-Dichlorodihydrofluorescein (DCFH) was used as a reactive oxygen species indicator probe (purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.) to evaluate the ROS generation efficiency of photosensitizers under light irradiation.
[0048] Prepare a stock solution by dissolving 10 mg of DCFH powder in 5 mL of DMSO and diluting it to 10 μM with phosphate-buffered saline (PBS, pH 7.4) before use. Mix the AIE photosensitizer (final concentration 20 μM) prepared in Example 1 with the DCFH solution (10 μM) in a quartz cuvette and place it under a white light source (50 mW / cm²). 2 Irradiation was performed under the following conditions. Fluorescence emission intensity at 525 nm was recorded every 30 seconds using a fluorescence spectrophotometer (λex = 488 nm). A DCFH solution without photosensitizer was used as a negative control. Figure 4 As shown, under illumination, the DCF fluorescence intensity of the AIE photosensitizer group increased rapidly over time, while the negative control group showed no significant fluorescence enhancement under the same illumination conditions, indicating that the AIE photosensitizer of the present invention has a good ability to generate reactive oxygen species.
[0049] Example 3: Preparation of luminescent suture This embodiment, based on Embodiments 1-2, utilizes the AIE photosensitizer prepared in Embodiment 1 to prepare a tendon-like layered spiral luminescent suture, specifically including the following steps: Step S1: Preparation of collagen aggregates Take 50 g of fresh bovine tendon, remove fat and connective tissue, rinse thoroughly with deionized water, and cut into 1×1 cm pieces. Place the pieces in 500 mL of 0.5 M acetic acid solution and soak at 4°C for 48 h to allow the tendon tissue to fully swell. After swelling, remove the tendon pieces and rinse three times with deionized water to remove residual acid from the surface. Place the treated tendon pieces in a homogenizer, add 200 mL of deionized water, and homogenize at 10,000 rpm for 5 min to obtain a collagen aggregate dispersion. Step S2: Preparation of spinning solution 18 g of polyvinyl alcohol (PVA) was dissolved in 82 g of deionized water and stirred at 90 °C for 3 h to obtain a PVA solution with a mass fraction of 18%. The solution was cooled to room temperature and stirred at 40 °C for 0.5 h to mix thoroughly. The AIE photosensitizer prepared in Example 1 was dissolved in DMSO to prepare a 2 mM solution, which was slowly added dropwise to the above mixture at 5% of the total volume of the spinning solution, and stirring was continued for 3 h. The resulting mixture was degassed in a vacuum drying oven at 25 °C and 0.8 MPa for 3 h, and then ultrasonically degassed in an ultrasonic cleaner for 2 h to obtain the spinning solution. Step S3: Wet spinning to prepare nascent fibers The spinning solution prepared in step S2 was transferred to a 10 mL syringe, fitted with a 25G three-lumen needle (inner diameter approximately 0.5 mm), and the syringe was fixed to a micro-injection pump. A coagulation bath was prepared: anhydrous sodium sulfate was added to deionized water and heated to 70°C to prepare a saturated sodium sulfate solution (approximately 30 g / 100 mL water). The injection pump was used to extrude the spinning solution at a rate of approximately 2 mL / h into the 70°C saturated sodium sulfate coagulation bath. The spinning solution underwent instantaneous phase separation and gelation in the coagulation bath, forming continuous fibers. The nascent fibers were initially drawn using a two-roller drawing system (speeds of 12 rpm and 14 rpm). The drawn fibers were washed with water to remove salt, and the washed fibers were collected at 20 rpm and dried in a 60°C oven for 12 h to obtain single nascent fibers. The average diameter of the nascent fibers was measured to be 100 ± 20 μm.
[0050] Step 4: Twisting and Assembly Thirty nascent fibers prepared in step S3 were taken and twisted unidirectionally at 25 rpm using a take-up twisting device until the fiber bundle formed a tight helical structure. After twisting, both ends of the fiber bundle were fixed and set in a 60℃ oven for 2 hours to obtain a tendon-like layered helical luminescent suture. The morphology and structure of the obtained tendon-like layered helical luminescent suture are as follows. Figure 5 As shown in the scanning electron microscope image, multiple fibers are twisted to form a uniform helical bundle structure, similar to the hierarchical arrangement of collagen fiber bundles in natural tendons. This structure enhances the interfiber bonding force, improves load transfer efficiency, and endows the suture with excellent mechanical strength and fracture resistance.
[0051] Example 4: Mechanical property testing of luminescent sutures The mechanical properties of the luminescent suture prepared in Example 3 were tested using a servo universal tensile testing machine, in accordance with the national standard "Textiles - Tensile Properties of Fabrics - Part 1: Determination of Breaking Strength and Elongation at Break (Strip Method)" (GB / T 3923.1-2013). Suture samples with single nascent fibers, 10 twisted fibers, 20 twisted fibers, and 30 twisted fibers were prepared, with five parallel samples tested for each type. Test conditions: initial clamp distance 130 mm, tensile speed 50 mm / min, ambient temperature 25±2℃, relative humidity 50±5%. Load-displacement data were recorded, converted into stress-strain curves, and tensile strength and elongation at break were calculated.
[0052] Test results are as follows Figure 6 As shown: the tensile strength of a single nascent fiber was 38.76 ± 5.23 MPa, and the elongation at break was 18.45 ± 3.12%; the tensile strength of 10 twisted sutures was 98.54 ± 8.67 MPa, and the elongation at break was 25.67 ± 2.98%; the tensile strength of 20 twisted sutures was 156.32 ± 10.21 MPa, and the elongation at break was 32.45 ± 3.45%; the tensile strength of 30 twisted sutures was 211.17 ± 12.35 MPa, and the elongation at break was 39.13 ± 3.67%. These results indicate that with the increase of the number of twisted fibers, the tensile strength and elongation at break of the suture significantly increase. The tensile strength of 30 twisted sutures is approximately 5.45 times that of a single fiber, demonstrating the mechanical reinforcement effect of the tendon-like helical structure. This demonstrates that the hierarchical spiral fiber bundle structure constructed by the present invention can effectively improve load transfer efficiency and enhance the synergistic load-bearing capacity between fibers, thereby significantly improving the mechanical properties of the suture.
[0053] Example 5: In vitro antibacterial activity test of luminescent sutures The antibacterial properties of the luminescent suture prepared in Example 3 were evaluated using the plate colony counting method. Gram-positive Staphylococcus aureus (S. aureus) was selected as the suture. Staphylococcus aureus ATCC 6538) and Gram-negative Escherichia coli ( Escherichia coli The test strains included methicillin-sensitive and methicillin-resistant strains (MRSA, ATCC 8739). Each strain was inoculated into LB liquid medium and cultured overnight at 37°C in a shaker until the logarithmic growth phase. The bacterial culture was then diluted with PBS buffer to approximately 1 × 10⁻⁶. 7 CFU / mL.
[0054] Thirty twisted sutures prepared in Example 3 were cut into 1 cm lengths and sterilized by UV irradiation for later use. A suture sample (0.1 g) was placed in a 2 mL centrifuge tube containing 1 mL of bacterial suspension. The experiment was divided into two groups: the light group used a white LED light source (wavelength 400-700 nm, light power density 50 mW / cm²). 2 The experimental group was irradiated for 10 minutes; the control group was not irradiated and was kept in the dark for 10 minutes. After treatment, the bacterial suspension was serially diluted 10-fold with PBS, and 100 μL of the diluted solution was spread on the surface of LB solid medium and incubated upside down in a 37℃ incubator for 12 hours. The number of colonies on each plate was counted, and the antibacterial rate was calculated using the formula: Antibacterial rate (%) = (number of colonies in the control group - number of colonies in the experimental group) / number of colonies in the control group × 100%. Each group had 3 replicates, and the experiment was repeated 3 times.
[0055] Test results are as follows Figure 7 As shown, under no light exposure, the suture of this invention exhibits only weak antibacterial activity; however, under light exposure, the luminescent suture demonstrates excellent bactericidal effects against both Staphylococcus aureus and Escherichia coli, with antibacterial rates exceeding 98%. This indicates that the suture's antibacterial activity is limited under no light exposure. These results prove that the AIE photosensitizer introduced in this invention can efficiently generate reactive oxygen species (ROS) under light exposure, thereby disrupting bacterial cell membrane structures and leading to bacterial death, thus giving the suture excellent photodynamic antibacterial properties.
[0056] Example 6: Evaluation of the cell compatibility of luminescent sutures Referring to the national standard "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity Tests" (GB / T16886.5-2017), the cell compatibility of the luminescent sutures prepared in Example 3 was evaluated using the CCK-8 method. Thirty sterilized twisted sutures were immersed in DMEM complete medium (containing 10% fetal bovine serum and 1% penicillin antibiotics) at a mass-to-volume ratio of 0.1 g / mL and incubated at 37°C in a 5% CO2 incubator for 24 hours. The supernatant was filtered through a 0.22 μm filter membrane for sterilization to obtain the material extract.
[0057] Logarithmic growth phase L929 mouse fibroblasts (purchased from Shanghai Luwei Technology Co., Ltd.) were digested with trypsin and counted, with a count of 5 × 10⁻⁶ cells. 3Cells were seeded at a density of [number] cells / well in 96-well plates, with 100 μL of DMEM complete medium added to each well. The plates were incubated at 37°C with 5% CO2 for 24 hours. The original medium was discarded. 100 μL of material extract was added to each well of the experimental group, an equal volume of fresh DMEM complete medium was added to the control group, and cell-free medium was added to the blank group. Each group had 6 replicates. On days 1, 3, and 5 of incubation, 10 μL of CCK-8 reagent was added to each well, and incubation continued for 2 hours. The absorbance at 450 nm was measured using a microplate reader, and cell viability was calculated as follows: Cell viability (%) = (Experimental group OD value - Blank group OD value) / (Control group OD value - Blank group OD value) × 100%.
[0058] Test results are as follows Figure 8 As shown, cells in all experimental groups maintained good growth during culture. After 1, 3, and 5 days of culture, the cell viability in the groups treated with the extract of the luminescent suture of this invention remained above 90%, reaching over 100% at some time points, with no significant difference compared to the control group. This indicates that the luminescent suture of this invention has no significant toxic effect on L929 cells and exhibits good cell compatibility.
[0059] Example 7: Evaluation of the in vitro degradation performance of luminescent sutures The degradation performance of luminescent sutures was evaluated using an in vitro enzymatic hydrolysis assay. Simulated digestion solution preparation: Pepsin (approximately 3000 U / mg activity) was dissolved in 0.1 mol / L hydrochloric acid solution to prepare a 1% pepsin solution, which was preheated to 37°C before use. Thirty twisted suture samples were weighed and recorded as W0 (approximately 5.9 mg). The samples were immersed in deionized water and gently squeezed to ensure complete saturation and remove internal air. Excess surface moisture was blotted with filter paper, and the samples were placed in a glass bottle containing 20 mL of preheated digestion solution. The bottle was placed in a 37°C constant-temperature shaker and continuously shaken at 150 r / min. Samples were removed every 5 days, washed three times with deionized water, freeze-dried, and weighed. The residual mass was recorded until the samples were completely degraded. Three replicates were prepared for each group.
[0060] Degradation curves as follows Figure 9 As shown, the sample mass gradually decreased with prolonged degradation time, and the sample was completely degraded on day 35. These results indicate that the luminescent suture of this invention has good controllable biodegradability, with a degradation cycle of approximately 30-35 days, which matches the skin wound healing cycle.
[0061] Example 8: The healing-promoting effect of luminescent sutures on an MRSA-infected wound model A full-thickness skin incision model of MRSA infection was established using male Sprague-Dawley (SD) rats (200-250 g, purchased from Shanghai Luwei Technology Co., Ltd.) to evaluate the healing-promoting effect of luminescent sutures. The experimental animals were randomly divided into four groups of six animals each: a blank control group (Control), a blank control light-illuminated group (Control-L), a suture group (PCT), and a suture light-illuminated group (PCT-L). All surgical instruments were sterilized by high-temperature autoclaving.
[0062] Rats were anesthetized by intraperitoneal injection of sodium pentobarbital (50 mg / kg), and their backs were prepared and disinfected. A longitudinal full-thickness skin incision, approximately 4 cm in length, was made on each side of the midline of the back. The wounds were intermittently sutured using different sets of 3-0 sutures, with 4 sutures per wound. After suturing, MRSA bacterial solution (1×10⁻⁶) was dripped onto each suture node. 7 CFU / mL, 10 μL) was used to construct an infected wound model. For the light-treated groups (Control-L and PCT-L), rats were immediately placed under a white light source (50 mW / cm²) after inoculation with the bacterial solution. 2 The rats in the non-light-exposed group were irradiated for 20 minutes; the rats in the non-light-exposed group were placed back into their cages immediately after the bacterial solution was added. The rats in each group were housed in separate cages and fed antibiotic-free food and water.
[0063] Wound healing was observed on postoperative days 1, 3, 5, 7, and 10. Photos of the wound were taken with a digital camera, and the wound area was measured using ImageJ software. The wound healing rate was calculated as follows: Wound healing rate (%) = (initial wound area - current wound area) / initial wound area × 100%.
[0064] Observation results as follows Figure 10 As shown, all four wound groups healed gradually over time, indicating that the wounds entered the normal healing process. Compared with the control group, the PCT group and the PCT-L group showed a faster wound healing trend in the middle and late stages. Among them, the PCT-L group showed the best wound healing effect after the fifth day, and the residual wound was the smallest by the tenth day, with continuous and smooth granulation tissue forming on the surface and inconspicuous scars. The results indicate that the suture of the present invention can effectively promote wound healing.
[0065] Example 9: Dynamic fluorescence tracking and degradation monitoring of luminescent sutures under mouse skin The subcutaneous fluorescence tracking ability of luminescent sutures was evaluated using Kunming mice (female, weighing 25-30 g, purchased from Shanghai Luwei Technology Co., Ltd.). Mice were randomly divided into two groups of five each: the suture group (PCT) and the suture illumination group (PCT-L). Mice were anesthetized with sodium pentobarbital, and their backs were prepared and disinfected. A subcutaneous incision of approximately 1 cm was made on the back, and a small sac was formed by separating the subcutaneous tissue with sterile forceps. Thirty twisted sutures, approximately 1 cm long, were inserted into the sac, and the skin incision was then sutured with non-absorbable sutures. For the PCT-L group, observation and photography were performed immediately after suturing under a 365 nm UV lamp; the PCT group served as a control and received no special treatment.
[0066] Fluorescence signals at the sutures were observed under natural light and 365 nm UV light on days 1, 3, 7, 11, and 15 post-implantation, and fluorescence images were acquired using a small animal in vivo imaging system (λex=450 nm, λ_em=590 nm). During the observation period, PCT-L group mice were subjected to light exposure (365 nm UV light, irradiation time <30 seconds) every 3 days, and were fed normally for the rest of the time.
[0067] Imaging results as follows Figure 11 As shown: Under natural light, the sutures are not directly observable subcutaneously; however, under 365nm UV light, the sutures emit bright orange fluorescence and can be clearly located subcutaneously. With prolonged implantation time, the fluorescence signal gradually weakens and shortens, consistent with the suture degradation process. Local fluorescence signals were still detectable on day 15 post-implantation, indicating that the sutures maintained good optical traceability throughout the observation period. H&E staining was performed on the subcutaneous wound (…). Figure 12 The results showed that the skin tissue in the PCT-L group maintained an intact tissue structure and clear hierarchical characteristics, with no obvious epithelial dysplasia or pathological keratosis, indicating that the suture had good tissue compatibility. These results demonstrate that the luminescent suture of this invention possesses excellent subcutaneous visualization monitoring capabilities, reflecting its degradation process in vivo through changes in fluorescence signals, while also exhibiting good tissue compatibility, providing a feasible strategy for non-invasive dynamic tracking of implanted suture materials after surgery.
[0068] Example 10: Verification of the preferred parameter range (1) Optimal volume ratio of PVA to CAs Following the preparation method of Example 3, with other parameters kept constant, suture samples with different PVA to CA ratios of 1:3, 1:2, 1:1, 2:1, and 3:1 were prepared, and their mechanical properties and spinnability were tested. The results showed that at a volume ratio of 1:3, the fiber strength was low (<20 MPa) and spinnability was poor; at a volume ratio of 1:2, the fiber strength reached over 80 MPa and spinnability was good; at a volume ratio of 2:1, the fiber strength was optimal (single fiber >100 MPa); and at a volume ratio ≥3:1, the collagen content was too low and the bioactivity was insufficient. Therefore, a volume ratio of 2:1 is preferred.
[0069] (2) Optimal selection of coagulation bath temperature Following the preparation method of Example 3, with other parameters kept constant, suture samples were prepared by setting the coagulation bath temperature to 50℃, 60℃, 70℃, 80℃, and 90℃. The results showed that below 60℃, phase separation was slow, fiber formation was insufficient, and the surface was rough; within the temperature range of 60-90℃, fiber formation was good, and the surface was smooth; above 90℃, collagen aggregates were prone to thermal denaturation, leading to a decrease in fiber mechanical properties. Therefore, a coagulation bath temperature of 70℃ is preferred.
[0070] 11.3 Optimal Selection of the Number of Twisted Threads Following the preparation method of Example 3, with other parameters kept constant, suture samples were prepared by setting the number of twists to 10, 20, 30, 40, and 50, respectively, and their mechanical properties and wire diameter were tested. The results showed that when the number of twists increased from 10 to 30, the tensile strength increased from 98 MPa to 211 MPa, and the wire diameter increased from 0.2 mm to 0.6 mm. When the number of twists increased to more than 40, the wire diameter exceeded 0.8 mm, which is not conducive to routine clinical suturing operations, and the improvement in mechanical properties tended to plateau. Therefore, a twist count of 30 is preferred.
[0071] The above content is only for illustrating the technical concept of the present invention and should not be construed as limiting the scope of protection of the present invention. Any modifications made to the technical solution based on the technical concept proposed in this invention shall fall within the scope of protection of the claims of this invention.
Claims
1. An aggregation-induced emission photosensitizer, characterized in that, It has the following structural formula: 。 2. The aggregation-induced emission photosensitizer according to claim 1, characterized in that, The photosensitizer is a compound having a donor-π-acceptor structure.
3. A tendon-inspired layered spiral luminescent suture, characterized in that, The suture material comprises the aggregation-induced emission photosensitizer as described in claim 1 or 2.
4. The tendon-like layered spiral luminescent suture according to claim 3, characterized in that, The suture is formed by twisting multiple nascent fibers to form a helical fiber bundle structure; the material of the nascent fibers also includes collagen aggregates and polyvinyl alcohol; the collagen aggregates are collagen fiber aggregates that retain the mesoscale fiber assembly structure of natural tendons.
5. The tendon-like layered spiral luminescent suture according to claim 4, characterized in that, The volume ratio of polyvinyl alcohol to collagen aggregates in the nascent fibers is 2:1; the number of twisted nascent fibers in the helical fiber bundle structure is 20-40.
6. A method for preparing a tendon-like layered spiral luminescent suture according to any one of claims 3 to 5, characterized in that, Includes the following steps: Step S1: Degrease and cut the animal tendon, treat it with acid, and then homogenize it to obtain a collagen aggregate dispersion; Step S2: Mix the polyvinyl alcohol solution with the collagen aggregate dispersion, add the aggregation-induced emission photosensitizer according to claim 1 or 2, stir evenly and then degas to obtain the spinning solution; Step S3: The spinning solution is extruded into a coagulation bath for phase separation and solidification, and then drawn, washed and dried to obtain nascent fibers; Step S4: Twist and twist the nascent fibers to form a helical fiber bundle structure, thus obtaining the suture.
7. The method for preparing a tendon-like layered spiral luminescent suture according to claim 6, characterized in that, In step S2, the volume ratio of the polyvinyl alcohol solution to the collagen aggregate dispersion is 1~2:1, and the concentration of the aggregation-induced emission photosensitizer in the spinning solution is 2 mM.
8. The method for preparing a tendon-like layered spiral luminescent suture according to claim 6, characterized in that, In step S3, the coagulation bath is a saturated sodium sulfate solution at 60~90℃.
9. The method for preparing a tendon-like layered spiral luminescent suture according to claim 6, characterized in that, In step S4, the number of twisted strands is 20 to 40, and the twisting speed is 20 to 30 rpm.
10. The use of the aggregation-induced emission photosensitizer according to claim 1 or 2 or the tendon-like layered spiral luminescent suture according to any one of claims 3-5 in the preparation of surgical suture materials.